Brain death in neonates: a case report - Georgios Mitsiakos; Ilias Chatzioannidis; Eirini Tzimou (Hygeia Press di Corridori Marinella, 2014)
Brain death (BD) is the permanent and complete loss of cerebral and brainstem function. It is relatively uncommon in newborns with its percentage among deaths being 1-6.3%. BD leads to debate for medical, ethical and philosophical issues. It is a challenging condition in neonatal intensive care units (NICUs) since difficulties for BD diagnosis in neonates and ever more so in preterm neonates do arise. Revised guidelines for BD diagnosis definition include history with known etiology, clinical examination, apnea testing and neurological evaluation often assisted by ancillary tests. We present the case of a near term female baby that was born with brain death due to hypoxic ischemic encephalopathy. We conclude that BD in newborns is a challenge to NICUs and there is a need for establishing and implementing new guidelines and checklists on national basis.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou